THE INFLUENCE OF GRAIN REFINER ON DENDRITE ARM SPACING OF ALUMINUM ALLOY ADC 12 - Bambang Suharno; Is Prima Nanda; Sri Harjanto; Erika Lirachandra (Jurnal Sains Materi Indonesia, 2007)
THE INFLUENCE OF GRAIN REFINER ON DENDRITE ARM SPACING OF ALUMINUM ALLOY ADC 12. ADC 12 is the common used materials for die casting process in producing automotive components. Grain refiner was added to aluminum ADC 12 to increase mechanical properties by decreasing grain size and improving fine distribution of gas porosity. Grain refiner also give positive effect in aluminum fluidity, where the proper addition of grain refiner will increase the fluidity. The purpose of present research is determining correlation between grain refiner addition and dendrite arm spacing, which also indirectly related to the grain size. 100% scrap of aluminum ADC12 and Al5Ti1B grain refiner were used as raw materials. Melting process has been done in a 1400 gr crucible with cokes and oxygen as the fuming energy. Argon was introduced into crucible at least in 1 minute for degassing. After degassing process accomplished, 0, 0.05, 0.1, 0.15, 0.2 % grain refiner Al5TiB, which have been choosen as experimental variable, were charged into crucible. Vacuum suction machine has been utilized to measure the aluminum fluidity at 680 0C, the common ADC 12 pouring temperature. Samples for microstructural analysis were tooken at the tip of specimen from vacuum suction test. Measurement of dendrite arm spacing (DAS) was conducted by SIGMA SCAN Pro.5 Software. The result indicated that at 680 0C, the addition up to 0.15% Al5Ti1B grain refinement reduced 50% dendrite arm spacing from 8.8 ìm (without grain refiner) to 4.5 ìm. Over 0.15% Al5Ti1B, the refinement stopped and DAS increased caused by the complex intermetallic phase (Ti-Al, Ti-B) has nucleated from the excess grain refiner.